Memoriam: Brendan Walsh - SSISI (Statistical and Social Inquiry Society of Ireland, 2016)
Memoriam: Brendan Walsh - 53rd President of the Statistical and Social Inquiry Society of Ireland (2001-2004) - Born: May 1942 (Dublin); Died: 20th May 2016 (Dublin)
Keywords: 314.15